Scoping Review: Layanan Perinatal Mental Health oleh Bidan di Negara ASEAN - Evilia Nur Savitri; Elli Nur Hayatiin; Menik Sri Daryanti (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Women are vulnerable to mental health disorders in the perionatal period due to changes in the role of being a mother. Midwives plays a pivotal role in screening and educating a perinatal mental health disorders. This study aims to investigate the experience of midwives in providing perinatal mental health services in ASEAN countries. This study adopted a framework from Arksey and O'Malley which consists of 5 steps, i.e., identifying scoping review questions, identifying relevant articles, planning article selection, charting data, and presenting data or results, discussions and conclusions. The data were gathered through three databases namely Wiley, proQuest and PubMed. The articles were selected based on inclusion criteria: publications within 2011-2021 in Indonesian or English, articles that have gone through peer review stages, and primary articles. The critical appraisal stage employed a checklist from the Joanna Briggs Institute (JBI). The findings of this scoping review obtained 10 articles from Indonesia, Vietnam, Cambodia, Thailand, Singapore and Malaysia. Four themes emerged were: (1) the knowledge of midwives about perinatal mental health (level of knowledge, symptoms, internal and external causes, prevention), (2) screening services (roles and barriers), (3) handling services (experience of integrating maternity services and information systems, midwifery care in perinatal care services, and forms of social support), and (4) the role of the midwife in internal referral. Midwives in ASEAN already have perinatal mental health experience related to perinatal mental health knowledge, have screened, provided treatment through midwifery care, and made internal referrals in cases of mental health disorders. Midwives need to improve the capabilities and skills of perinatal mental health through education and training.